First principles calculations on the hydrogen atom passivation of TiO2 nanotubes. Issue 23 (17th February 2016) - Dai, Jianhong; Song, Yan
Abstract : Both charge and hydrogen atom passivation could metallize TiO2 nanotubes. Abstract : First principles calculations are carried out to study the hydrogen atom passivation properties of TiO2 nanotubes. The influence of charge on the stabilities of the TiO2 nanotubes with or without hydrogen atom passivation is studied. Two types of anatase TiO2 nanotube, denoted as ( m, 0) and (0, n ) ( m = 6, 9 and n = 3, 6), were considered in the present work. The formation energy of the charged systems and the adsorption energy of the hydrogen atoms are evaluated. The negatively charged (6, 0) nanotubes and one charge state containing (0, 3) nanotubes possess low formation energies, indicating that they are easy to form among the considered nanotubes. The electronic structures of the TiO2 nanotubes are analyzed using several methods. It was found that the adsorbed hydrogen atoms can easily donate electrons to the oxygen atoms of the TNTs. Furthermore, the charge and hydrogen atom passivation cause the diverse distribution of states around the Fermi energy level, and therefore, may expand the potential applications of TiO2 nanotubes.